Pengaruh Pemberian Minyak Cumi Pada Pakan Terhadap Respon Makan Ikan Kerapu Cantang (Epinephelus fuscoguttatus x Epinephelus lanceolatus) - Ricko Rionaldo; Tri Yulianto; Henky Irawan (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2021)
This study aims to determine the dose of squid oil attractant to increase the feeding response of grouper Epinephelus fuscoguttatus x Epinephelus lanceolatus. This research was conducted in March 2020 at the Fish Seed Center, Pengujan Village, Bintan Regency, Riau Islands Province. The method used was an experimental method with a completely randomized design (CRD) with 4 treatments and 3 replications, where treatment K: (Megami feed without attractants), treatment A: (Megami feed + 6 ml/kg of squid oil), treatment B : (Megami feed + 9 ml/kg squid oil), treatment C: (Megami feed + 12 ml/kg squid oil). Data analysis with Analysis of variance (ANOVA) and Duncan's continued test, showed that the fastest response of fish to feed was at a dose of 12 ml/kg or treatment C was the fastest treatment, the results obtained were at the level of feed consumption (99.23 Â± 0.67%) and survival rate (100 Â± 0.00%).